2010
DOI: 10.1093/humrep/deq149
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of cortical bone mineral density in women with polycystic ovary syndrome: a peripheral quantitative computed tomography (pQCT) study

Abstract: The PCOS women of our study seem to have a higher quality of bone material in the distal tibia and probably a better resistance of bone in the compression strength without alterations in bone mass and geometry (especially the lean PCOS women), indicating that our oligomenorrheic and hyperandrogonemic PCOS women may be protected from the development of osteoporosis and fracture risk later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
3
36
2
Order By: Relevance
“…Conversely, other studies report higher BMD in PCOS [13] consistent with testosterone inhibiting bone resorption in vivo [4] or through peripheral conversion to 17b-estradiol and estrone, effects of elevated insulin on osteoblast proliferation [14] or the higher prevalence of overweight and obesity in PCOS. It is possible that the effects of contraception on BMD may be worsened in the hyperandrogenic state of PCOS given that steroidal contraceptives reduce bioavailable androgens.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, other studies report higher BMD in PCOS [13] consistent with testosterone inhibiting bone resorption in vivo [4] or through peripheral conversion to 17b-estradiol and estrone, effects of elevated insulin on osteoblast proliferation [14] or the higher prevalence of overweight and obesity in PCOS. It is possible that the effects of contraception on BMD may be worsened in the hyperandrogenic state of PCOS given that steroidal contraceptives reduce bioavailable androgens.…”
Section: Discussionmentioning
confidence: 91%
“…Our study showed that lean women with PCOS had greater mean skeletal mass than control women. Peripheral quantitative computerised tomography established significantly higher distal-tibial cortical density in lean PCOS than that in lean control women, although trabecular bone density did not differ (Kassanos et al 2010). Good et al (1999) reported higher BMD in the left and right arms and left ribs of a lean PCOS group compared to control values.…”
Section: Discussionmentioning
confidence: 79%
“…In recent years, attention has centred on determining body composition in PCOS women with different body mass index, quantity and quality of bone mass and (Zborowski et al, 2000;Kirchengast et Huber 2001;Faulds 2003;Puder et al 2005;To and Wong 2005;Toscani et al 2007;Barber et al 2008;Cosar et al 2008;Moran and Teede 2009;Kassanos et al 2010;March et al 2010;Manneras-Holm et al 2011;Villa et al 2011 andFranks 2013). Our study presents analytic results of investigations into body composition and somatotype in lean PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The static levels of estradiol, with the absence of estradiol peak associated with ovulation in PCOS women, may negatively affect bone density and geometry. 6,7 Although conflicting results have been reported so far bone mass and density in PCOS women appear to be maintained at a level comparable to normal ovulatory women or even higher. 8e10 A higher bone mass might be related to a higher body mass index (BMI), higher estrogen and androgen levels and hyperinsulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…11 In peripheral quantitative computed tomography (pQCT) studies a trend for higher cortical and total bone cross-sectional area (CSA) was found in lean and obese PCOS women. 7 At present there is no approved therapy for PCOS in adolescents. Ib añez et al described a treatment combination of low-dose flutamide, metformin and etinylestradioldrosperinone (oral contraception with antiandrogen effect).…”
Section: Introductionmentioning
confidence: 99%